Amplifying Influence: The Role of Brand Ambassadors in the Relationship Between Korean Wave and K-Pop Merchandise Purchase Decisions - Fatma Kurnianingtyas, Lintang; Faruqi, Faris (Marketing and Business Strategy, 2025)
The purpose of this study is to ascertain how brand image, electronic word-of-mouth, and the Korean wave affect consumer choices for K-pop merchandise with Brand Ambassadors as moderator variables for the case study at X in East Jakarta. This research uses an associative research strategy. The data collection technique is through a questionnaire with a simple random sampling technique. The SEM-PLS method was used to analyze the data.  All customers who have bought NCT K-Pop items make up the research population.  There were 260 samples in total, chosen by multiplying the number of indicators by 10.  The study's findings indicate that buying decisions are significantly influenced by the Korean Wave, brand image, and brand ambassadors. Electronic word-of-mouth has no discernible impact on purchasing decisions.  Other than that a Brand Ambassador is able to moderate the significant influence of the Korean Wave. At the same time, Brand Image and Electronic word of mouth are indirectly unable to moderate Purchase Decisions.